Optimization of a Liquid Crystal‐based Sensory Platform for Monitoring Enzymatic Glucose Oxidation. (27th April 2016) - Wei, Yibin; Jang, Chang‐Hyun
Abstract : Managing glucose levels in human blood is extremely important for the treatment of diabetes. Here, an innovative sensory strategy has been developed to monitor the enzymatic activities of glucose and glucose oxidase by using confined liquid crystal (LC) birefringent droplet patterns. Acidic products released during the glucose oxidation process lead to a slight decrease in the pH of aqueous systems that can be monitored by pH‐sensitive LC materials. Of the existing pH‐sensitive LC materials, dodecanoic acid‐doped 4‐cyano‐4′‐pentylbiphenyl is inexpensive and easily adjusted to satisfy the 7.4 ± 0.05 pH requirement of human blood. Moreover, the orientational alignment of capillary‐confined pH‐responsive LCs can be disrupted at the aqueous/LC interface following a slight decrease in the critical pH of aqueous reaction systems, which results in an optical signal that can be observed with the naked eye by using polarizing optical microscopy. Based on the stable LC droplet patterns generated by the cylindrical confinement system, the functionalized LCs can selectively detect glucose at concentrations as low as 0.1 pM. This study further advances the previously reported LC‐based glucose monitoring systems by reducing production costs and instituting a smarter LC sensory design. This improved system shows potential for the use in clinical bioassay applications. Abstract :